The inter-relationship between CEOs’ birthplaces and financial performances of firms. - Quang Huy, Pham. (2011)
Chief Executive Officers (CEOs) are highly exceptional individuals with talents and abilities acquired and developed from varied environments. This study examines the relationships between the birthplaces of nearly 400 American CEOs and their effects on firms’ performances, by analyzing the livability factor of CEOs’ birth states and comparing the performances of firms managed by local-born versus non-local-born CEOs. We employed linear regressions on publicly available data such as financial performances of Standard & Poor’s Top 500 companies for the 1993-2006 period as well as CEOs’ background information to conduct our investigation. Our results provide evidence that there are differences in the performances of firms managed by CEOs born in different states of the United States (U.S.) and that generally, firms managed by CEOs born in more livable states perform worse than those managed by CEOs born in less livable states. In addition, we discovered that there is no difference between the performances of firms managed by local CEOs and those managed by non-local CEOs after controlling for factors such as firms’ characteristics, industrial and macro-economic effects. Overall, our research has born implications on CEO selection within the U.S. and gives additional insights to hiring committees for assessing CEO applicants.